SISTEM INFORMASI PENERIMAAN DAN PENGELUARAN KAS PADA PARIWISATA WAYANG WINDU BERBASIS DESKTOP - Syafira, Annisa Nanda; Paryati, Retno (Jurnal Mahasiswa Terapan; Vol 1 No 2 (2025): Jurnal Mahasiswa Terapan, 2025)
This research aims to analyze, design, implement, and test a cash receipt and disbursement information system tailored to the operational needs of Wayang Windu Tourism. The study employs the Waterfall development method with data collected through observation, interviews, documentation, and literature review. The analytical framework used is PIECES analysis, and the system is designed using process modeling tools such as Flowcharts and Data Flow Diagrams (DFD). The programming language utilized Visual Basic for Applications. The findings reveal that the previous cash management system at Wayang Windu Tourism lacked proper documentation, including proof of cash in and cash out, leading to frequent errors in recording cash flows and inaccurate financial information. The proposed system, developed with Visual Basic for Applications, simplifies cash management by providing structured outputs, including cash receipt reports, cash disbursement reports, and supporting documentation like proof of cash transactions. However, the system does not yet accommodate the display of cumulative balances from previous months when managing end-of-month balances. Users only need to input transaction data, which the system processes automatically to generate comprehensive reports. Testing results indicate that the new Cash Receipt and Disbursement Information System functions effectively and meets the intended objectives, enhancing operational accuracy and efficiency.